Chemical Characterisation, Organic Acids by HPLC, Fatty Acids by GC-GCMS and Antioxidant Activity of Commonly Consumed Leafy Vegetables in India - Pamidighantam, Prabhakara Rao (Fakultas Farmasi, Universitas Gadjah Mada, 2018)
Chemical, organic acids, fatty acid composition and antioxidant activity of commonly consumed leafy vegetables such as Hibiscus cannabinus, Rumex vesicarius, Basella rubra and Alternanthera sessilis were investigated. High performance liquid chromatography (HPLC) was used to quantify organic acids in leaf powders. Protein and fibre contents of Alternanthera sessilis leaf powder were the highest (31.2, 12.5% respectively) and lowest in Hibiscus cannabinus leaf powder (20.86 and 3.94%) among the leaf powders analysed. Oxalic acid was found to be the dominant acid in all the leafy vegetable powders and it was maximum in Alternanthera sesilis (10733 mg/100g) and Basella rubra (23331 mg/100g) powders. Gas and mass chromatography (GC-MS) analysis of leaf powder lipids were rich in palmitic (14.6 – 24.2%), linolenic (25.6 -56.9%), linoleic (15.4-21.1%) and oleic (2.6 - 13.7%) acids. Hibiscus leaf powder exhibited maximum inhibition of 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical with 95% inhibition at 2.8 mg/ml concentration and assay 92% of ABTS (2, 2-Azinobis-3-ethyl Benzothiazoline-6-Sulfonic acid) diammonium salt) at 0.6mg/ml concentration.